The Urgency of Rijal Al-Hadis in the Contemporary Era - M. Dun, Ummulkhairy; Askar, Romlah; Suparta, Suparta (Cerdika: Jurnal Ilmiah Indonesia, 2025)
In the development of Islamic knowledge, hadith holds a central role as the second source of Islamic law after the Qur’an. To ensure its authenticity, the study of Rijal al-Hadith—biographical evaluation of hadith narrators—becomes essential, especially in the contemporary era where the spread of weak and fabricated hadiths is a growing concern. This research aims to analyze the concept, methodology, and relevance of Rijal al-Hadith as a scientific discipline that verifies the credibility of narrators through two main approaches: tarikh al-ruwah (narrator biography) and jarh wa ta’dil (narrator criticism). Using qualitative methods and a literature review approach, the study gathers references from classical and modern Islamic scholarship to examine how Rijal al-Hadith can serve as a critical tool in maintaining the integrity of hadith literature. The findings show that Rijal al-Hadith plays a crucial role in identifying authentic narrations, preventing misinterpretations, and strengthening critical thinking in Islamic discourse. It emphasizes that Muslims today must go beyond merely quoting hadith and instead understand the science behind its authentication. The study concludes that Rijal al-Hadith remains highly relevant and should be reintroduced in modern Islamic education to build intellectual resilience and prevent the misuse of religious texts. Future studies are recommended to integrate digital tools in mapping narrator chains and enhance accessibility to hadith authentication resources.